GLOBECOM '05. IEEE Global Telecommunications Conference, 2005. 2005
DOI: 10.1109/glocom.2005.1577896
|View full text |Cite
|
Sign up to set email alerts
|

Low PAPR full-diversity space-frequency codes for MIMO-OFDM systems

Abstract: Use of precoding transforms such as Hadamard Transforms and Phase Alteration for Peak to Average Power Ratio (PAPR) reduction in OFDM systems are well known. In this paper we propose use of Inverse Discrete Fourier Transform (IDFT) and Hadamard transform as precoding transforms in MIMO-OFDM systems to achieve low peak to average power ratio (PAPR). We show that while our approach using IDFT does not disturb the diversity gains of the MIMO-OFDM systems (spatial, temporal and frequency diversity gains), it offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was shown that the system performance can be improved by adding such precoders at the transmitter. On the other hand, unitarty precoders, such as Hadamard and DFT matrices, have also been studied in [23], [24] for space-frequency coded OFDM (SF-OFDM) system. The space-time block coding technique has also been applied to single-carrier systems with multiple antennas [25]- [27].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the system performance can be improved by adding such precoders at the transmitter. On the other hand, unitarty precoders, such as Hadamard and DFT matrices, have also been studied in [23], [24] for space-frequency coded OFDM (SF-OFDM) system. The space-time block coding technique has also been applied to single-carrier systems with multiple antennas [25]- [27].…”
Section: Introductionmentioning
confidence: 99%